Environmental journalism and the struggle against disinformation in Brazil: navigating digital hostility and climate crisis coverage - Sarmento, Claudia (Frontiers in Communication, 2026)
This study investigates how Brazilian journalists covering socio-environmental issues are affected by disinformation campaigns linked to far-right populism and lobbies opposing environmental protection. Based on in-depth interviews with 14 professionals specializing in environmental reporting, it analyzes how they perceive the digital hostility aimed at delegitimizing journalism and science. Although they do not feel silenced, participants report frustration and difficulties in responding to manipulative narratives. The accounts suggest that environmental coverage has become a field of symbolic dispute, particularly during the Bolsonaro administration, making disinformation a structural problem that affect daily journalistic routines. Strategies such as investigative reporting that expose economic interests, empathetic storytelling and the use of accessible language without falling into partisan disputes are seen as ways to confront this scenario of information disorder.